2016
DOI: 10.1007/s10508-016-0733-3
|View full text |Cite
|
Sign up to set email alerts
|

Older Male Clients of Female Sex Workers in the United States

Abstract: Recent research has provided increased information about the clients of sex workers; however, little is known about the population of older male customers who contract for heterosexual services online. Clients (N = 208) between 60 and 84 years of age were obtained through sex work review sites and online discussion forums. Participants completed a 129-item questionnaire focusing on physical health, sexual and non-sexual behaviors with sex providers, and the qualities sought in the same. More than half reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
(37 reference statements)
0
28
1
Order By: Relevance
“…Sanders finds that regulars, men who return to the same providers for services, talk about escaping from the dominant roles they often play in their other worlds, and it was not a discourse of entitlement (Sanders, 2008b). Studies of clients in indoor markets find similar patterns, that clients view paying for sex more as one would other consumer services, using their consumer power to meet physical, sexual, emotional or social needs (Bernstein, 2007;Joseph & Black, 2012;Milrod & Monto, 2016;Milrod & Weitzer, 2012;Peng, 2007;Pettinger, 2013;Sanders, 2008aSanders, , 2008b. Valuing women's abilities as "professionals" seems to characterize clients in online markets as much as a desire for feminine services (Pettinger, 2011).…”
Section: Client Attitudes and Gender Inequalitymentioning
confidence: 99%
“…Sanders finds that regulars, men who return to the same providers for services, talk about escaping from the dominant roles they often play in their other worlds, and it was not a discourse of entitlement (Sanders, 2008b). Studies of clients in indoor markets find similar patterns, that clients view paying for sex more as one would other consumer services, using their consumer power to meet physical, sexual, emotional or social needs (Bernstein, 2007;Joseph & Black, 2012;Milrod & Monto, 2016;Milrod & Weitzer, 2012;Peng, 2007;Pettinger, 2013;Sanders, 2008aSanders, , 2008b. Valuing women's abilities as "professionals" seems to characterize clients in online markets as much as a desire for feminine services (Pettinger, 2011).…”
Section: Client Attitudes and Gender Inequalitymentioning
confidence: 99%
“…We reported that the prevalence of oral sex practiced by low-tier FSWs in this study was 21.9%. Since we only measured this prevalence during the previous month, we are not able to compare this result with overseas FSWs [14,15] or those in China [16], nor could we compare these data with those of common…”
Section: Discussionmentioning
confidence: 99%
“…We are not clear about the rate of condom use in oral sex, but could speculate that oral sex is much less protected than other sex practices. Foreign studies have shown that oral sex among FSWs and their clients is less protected [14,15]. One Chinese study revealed that 70.1% of FSWs always used condoms to protect themselves when they had vaginal sex with clients, and this figure was 57.9% for anal sex but only 22.7% for oral sex [16].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…While research specifically involving older clients is still sparse, initial findings from one survey have shown that the frequency of paid sex was positively associated with the advancing age of respondents (Milrod & Monto, 2016 (Wotton, 2016a).…”
Section: Demographicsmentioning
confidence: 99%